2005
DOI: 10.1111/j.1600-0420.2005.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Achiasmia and unilateral optic nerve hypoplasia in an otherwise healthy infant

Abstract: ABSTRACT. An 18-month-old white boy, observed by his parents at 1-2 months age to have poor visual attentiveness and nystagmus, underwent an ophthalmological evaluation. The patient also underwent unsedated 5-channel flash visual evoked potentials (VEP) and sedated electroretinogram (ERG) testing as well as magnetic resonance imaging (MRI) of the brain and orbits. The VEP in response to monocular stimulation demonstrated occipital asymmetry and was clearly suggestive of crossed asymmetry and also showed right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 15 publications
1
15
1
Order By: Relevance
“…A third, unilateral VEP asymmetry defined the absence of optic-nerve-fibre decussation at the chiasm from the one eye, while from the other eye with severe optic nerve hypoplasia, the VEP was absent. Such unilateral VEP asymmetry has been observed previously with flash stimulation in one child [11], although in the present study, this was observed with pattern onset stimulation in two of these achiasmatic children.…”
Section: Ocular Findings and Mri Characteristicscontrasting
confidence: 66%
See 3 more Smart Citations
“…A third, unilateral VEP asymmetry defined the absence of optic-nerve-fibre decussation at the chiasm from the one eye, while from the other eye with severe optic nerve hypoplasia, the VEP was absent. Such unilateral VEP asymmetry has been observed previously with flash stimulation in one child [11], although in the present study, this was observed with pattern onset stimulation in two of these achiasmatic children.…”
Section: Ocular Findings and Mri Characteristicscontrasting
confidence: 66%
“…Therefore, the lack of uniformity in VEP asymmetries shown previously has also been found in the present study. In the majority of previous studies, ipsilateral asymmetry was observed with flash and pattern onset stimulation [3][4][5][6][7], while crossed asymmetry and crossed contralateral positivity have also been associated with achiasmia [8][9][10][11][12]36]. In the present study, the ipsilateral asymmetry defines the absent optic-nervefibre decussation at the chiasm for both of the eyes.…”
Section: Ocular Findings and Mri Characteristicsmentioning
confidence: 47%
See 2 more Smart Citations
“…Cases have been reported with this anomalous asymmetry of response detected using the pattern onset VEP [1][2][3] and flash VEP [4][5][6][7][8], and similar cases have been reported in which the absence of the chiasm is the only significant abnormality (e.g. [9]).…”
Section: Discussionmentioning
confidence: 88%